Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan di Bank BJB Tamansari - Anugerah, Muhammad Fadhlan; Luturlean, Bachruddin Saleh (eProceedings of Management, 2024)
It is important for companies to make maximum efforts to obtain the required quality of human resources. Effortsthat can be made include managing human resources with the hope of achieving high productivity for the company.With work motivation and discipline, the company will achieve its best performance if its employees uphold highwork motivation and discipline. The purpose of this study is to determine and analyze the influence of workmotivation and work discipline on employee performance at Bank BJB Tamansari. The research method used isquantitative research with a descriptive-verification type. Sampling was done using a saturated sampling techniqueinvolving 100 employees of Bank BJB Tamansari. The data analysis techniques used were descriptive analysis andmultiple regression analysis. Based on the results of the descriptive analysis, it is shown that the variables of workmotivation, work discipline, and employee performance are in the good category. Therefore, it can be concludedthat work motivation and work discipline have a positive and significant relationship with employee performance atBank BJB Tamansari.Keywords-work motivation, work discipline, employee performance.